Rapid-onset central motor plasticity in multiple sclerosis - Zeller, Daniel; Aufm Kampe, K.; Biller, Armin; Stefan, K.; Gentner, R.; Schütz, A.; Bartsch, A.; Bendszus, Martin; Toyka, K. V.; Rieckmann, P.; Classen, J. (Neurology, 2010)
Objective: To study rapid-onset central motor plasticity, and its relationship to motor impairment and CNS injury in patients with multiple sclerosis (MS). - Methods: In this cross-sectional observational study, motor plasticity was examined neurophysiologically and behaviorally in 22 patients with moderately severe (median Expanded Disability Status Scale score 2.5 [0-6]) stable MS and matched healthy controls. First, plasticity was assessed using paired associative stimulation (PAS), a protocol modeling long-term synaptic potentiation in human cortex. PAS combines repetitive electric nerve stimulation with transcranial magnetic stimulation (TMS) of the contralateral motor cortex. Second, motor learning was tested by a force production task. Motor impairment was assessed by functional tests. CNS injury was evaluated by obtaining normalized N-acetyl-aspartate (NAA/Cr) spectra using magnetic resonance spectroscopy and by the corticomuscular latency (CML) to the abductor pollicis brevis muscle as tested by TMS. - Results: Patients with MS performed worse than controls in functional motor tests, CMLs were prolonged, and NAA/Cr was decreased. PAS-induced enhancement of corticospinal excitability and training-induced increments of motor performance were comparable between patients with MS and controls. Neither PAS-induced plasticity nor motor learning performance correlated with motor impairment or measures of CNS injury. Patients with high CNS injury and good motor performance did not differ significantly from those with high CNS injury and poor motor performance with respect to PAS-induced plasticity and motor learning success. - Conclusions: Despite motor impairment and CNS injury in patients with multiple sclerosis (MS), rapid-onset motor plasticity is comparable to that in healthy subjects. Compensation of MS-related CNS injury is unlikely to be constrained by insufficient rapid-onset neuroplasticity.